Job demands, emotional dissonance and elderly abuse: The moderating role of organizational resources. Issue 5 (20th October 2018) - Andela, Marie; Truchot, Didier; Huguenotte, Virginie
ABSTRACT: The present study focuses on elderly abuse committed by caregivers in nursing homes. It aimed at a better understanding of neglect and abusive behaviors by considering the working context and the emotional dissonance of these professionals. To achieve this goal, direct effects of emotional dissonance, job demands (workload and emotional demands) and organizational resources (high-quality relationships with the colleagues and the supervisor) on neglect and abusive behaviors were analyzed. Moreover, the moderating role of organizational resources was explored. The study was conducted among 481 nurses and healthcare assistants from different French nursing homes. Overall, results contributed to the literature by pointing out the impact of emotional dissonance and caregivers' working context on neglect and abusive behaviors. Moreover, results highlighted the moderating effect of high-quality relationships with the colleagues and the supervisor and give rise to potential implications in preventing elderly abuse in nursing homes.